Use of the virtual classroom and learnig mathematic in primary students of a state educational institution in Lima - Charry Aysanoa, Juan Marciano (2021)
The purpose of the article is to demonstrate the relationship between the use of the virtual classroom and the learning of mathematics in primary school students from a public educational institution in Lima, Peru. The study was developed according to the Positivist paradigm, taking the Quantitative approach. It corresponds to the basic type, non-experimental correlational design. The sample was represented by 120 sixth grade students, chosen intentionally, not probabilistically. To measure the variable: use of the virtual classroom, the survey technique was applied and, as an instrument, a questionnaire that measures the dimensions: incorporation of students, dynamization of teaching and achievements in virtual learning; presents a reliability of 0.972 (Cronbach's alpha). To measure the variable: learning of mathematics, a knowledge test was carried out, with 25 items (dichotomous scale), in the dimensions: mathematizes situations, communicates and represents mathematical ideas, develops and uses strategies. It has a reliability of 0.61 (Kuder-Richardson). Both instruments are valid (criteria of judges). The existence of a positive and significant relationship between the use of the virtual classroom and the learning of mathematics is reported (r = 0.825, where p value <0.05) in students of the sixth grade of Primary Education of the Educational Institution " María Reina” from Cercado of Lima, Peruvian. Likewise, there are positive and significant correlations between the virtual incorporation of students (r = 0.803), dynamization of teaching (r = 0.769) and achievements in virtual learning (r = 0.790) with the learning of mathematics.